Measurement by the physical educator why and how - Miller, David K. (David Keith) (WCB McGraw- Hill, 1998)
This practical text gives students a foundation in measurement and evaluation in physical education, showing them how to devise tests and techniques. The author explains how to measure physical performance, construct and select tests and grade students' performance.